Memorial exhibition in conjunction with 20th Ahmad Ibrahim Memorial Lecture hosted by Dar al-Hikmah Library - Tuan Ameri, Tuan Safa'at (Persatuan Pustakawan Malaysia (PPM), 2024)
On 7th March 2024, the 20th Ahmad Ibrahim Memorial Lecture unfolded at the Senate Hall of the International Islamic University Malaysia (IIUM) with the esteemed presence of Malaysia’s Attorney General, the Honourable Datuk Ahmad Terrirudin Mohd Salleh. The event, themed “Beyond Prosecution: The Attorney General’s Advisory Odyssey”, brought together a gathering of legal scholars, dignitaries, and practitioners eager to delve into the intricate realm of legal advisory practices in Malaysia.